ANALYSIS OF ONLINE DRIVER'S LICENSE SERVICES ON THE EFFECTIVENESS OF PUBLIC SERVICES IN THE DIGITAL AGE - Nur Savitri, Alifia; Haryati, Eny; Roekminiati, Sri (International Journal of Multidisciplinary Reseach, 2026)
The development of digital technology has driven the transformation of public services towards a more effective, efficient, and transparent system. One form of public service digitalization is the implementation of online driver's license (SIM) services through the National Precision Driver's License (SINAR) application developed by the Indonesian National Police Traffic Corps. This study aims to analyze the effectiveness of online driver's license services on public services in the digital era, particularly at the Sidoarjo Police Headquarters. The research method used is a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation involving 10 informants consisting of officers from the Sidoarjo Police Headquarters and the community as service users. Data analysis was carried out using a flow analysis model which included data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that the Online Driver's License service at the Sidoarjo Police Headquarters has been running well and effectively, in terms of timeliness, officer accuracy, and the manner of providing services to the community. Although there are still obstacles such as delays in printing due to running out of blank forms and technical problems, officers are able to provide solutions in the form of temporary driver's licenses so as to maintain public satisfaction. Thus, the Online Driver's License service contributes positively to improving the effectiveness of public services in the digital era.